CD71 surface analysis of T cells: a simple alternative for extracorporeal photopheresis quality control - Schwab, Laura; Michel, Gabriela; Bein, Gregor; Hackstein, Holger (Vox Sanguinis, 2019)
Background: Extracorporeal photopheresis (ECP) is a leukapheresis-based cellular therapy that is used with increasing frequency worldwide to treat various T-cell-mediated diseases. Currently, the inhibition of T-cell proliferation after photopheresis is analysed frequently using time-consuming assays including radioactive thymidine assays or carboxyfluorescein succinimidyl ester (CFSE) staining. We investigated whether simple surface T-cell staining using surrogate markers of T-cell proliferation can replace time-consuming measurement of T-cell proliferation in ECP quality control. Study design and methods: T-cell activation markers were investigated by flow cytometry after ECP. Candidates were validated by direct comparison with the classical CFSE T-cell proliferation inhibition test and apoptosis staining. Finally, surface T-cell staining was performed in patient samples in comparison with classical methods. Results: CD71 expression exhibited the fastest and most robust upregulation, which was detectable as early as 6–8 h after T-cell stimulation and almost completely abrogated by ECP. In a direct comparison with the CFSE T-cell proliferation assay, suppression of CD71 expression after ECP was almost identical and detectable as early as 16 h after stimulation in peripheral blood mononuclear cells of healthy donors. Furthermore, in direct comparison with classical apoptosis staining, the inhibition delta of CD71 after ECP was significantly higher. Moreover, in patients under T-cell suppressive therapy, T-cell-dependent CFSE and CD71 assays exhibited decreased sensitivity to detect ECP treatment and were inferior in comparison to apoptosis staining. Conclusion: Surface CD71 analysis represents a very simple quality control alternative to detect ECP-mediated T-cell proliferation inhibition in normal PBMC samples devoid of T-cell suppressive drugs.
CRIS-Team Scopus Importer:2019-11-19
Keywords: CD71; extracorporeal photopheresis; flow cytometry